The Educational Inspection in the Foral Community of Navarra - Indart Sarratea, Blanca Esther; Lasaosa Villanua, Santiago (Avances en Supervisión Educativa, 2009)
Navarra, is a uniprovincial community, with an approximate population of 620,000 habitants. 43% live in Pamplona and its region. The immigrant population accounts for approximately 10% of the total population. One of its hallmarks of this Community is to have two official languages depending on the geographical areas. The D.F. 159/88, develops the Law of the Basque language defining for non-university education the linguistic models A, B and D. In the aforementioned decree law the models A, B, D are authorized for the Basque-speaking area, therefore, the teaching of the Basque language is mandatory; for the mixed zone the models A, B, D and G and for the non-Basque-speaking area the models A and G.